Green synthesis of silver nanoparticles using Aidia densiflora leaf extract: characterisation and bioactivities - Zeheri, Ainul Hayati; Bakhtiar, M. Taher; Mohd Jailani, Muhammad Taufiq; Md Jaffri, Juliana; Darnis, Deny Susanti; Khotib, Junaidi (IIUM Press, 2025)
Introduction: Plant-mediated green synthesis of nanoparticles has become a promising option in green nanotechnology because it is simple, cost-effective, eco-friendly, and biologically effective. This study focused on the synthesis and characterisation of silver nanoparticles (AgNPs) using Aidia densiflora leaf extract, as well as the evaluation of their antimicrobial and cytotoxic activities. Methods: AgNPs were synthesised with A. densiflora leaf extract and their formation was confirmed using an ultraviolet–visible (UV–Vis) spectrophotometer. Liquid chromatography-mass spectrometry quadrupole time-of-flight was utilised for phytochemical profiling. The synthesised AgNPs were characterised using a zetasizer and zeta potential analyser, scanning electron microscopy-energy dispersive X-ray, Fourier Transform Infrared, X-ray diffraction (XRD), and thermogravimetric analysis. Antimicrobial activity of AD-AgNPs was tested against six microorganisms using the disc diffusion method, while cytotoxicity against MCF-7 human breast cancer cells was evaluated via MTT assay. Results: AgNP formation was confirmed by XRD and UV–Vis analysis, with absorbance peaks at 399–424 nm. Optimal synthesis was achieved using 10 mM AgNO? at 60°C and pH 7. SEM showed spherical-like nanoparticles averaging 96.06 nm with significant aggregation. The zeta potential was –35.6 mV, and XRD indicated a face-centred cubic structure with a crystalline size of 6.94 nm. AD-AgNPs showed no antimicrobial activity and low cytotoxicity. Conclusion: A. densiflora leaf extract can be used to synthesise AgNPs, however, further optimisation is required for better nanoparticle stabilisation and improvement of bioactivities